Pola Asuh Orang Tua Wanita Karir dalam Meningkatkan Kehidupan Keberagamaan Anak di Lingkungan Warga RW.05 Cijerah Bandung - Octavia Dwi Susanti; Aep Saepuddin; Khambali (UNISBA Press, 2021)
Abstract. This research is motivated by the large number of parents in the neighborhood of Rw.05 Cijerah Bandung who are busy working. Most of them leave their children's education to their families, educational institutions, or household assistants. As we know, religious education is a basic thing that must be given by parents to their children. Religious education in children is the beginning of personality formation, good or bad children depend on their parents and the environment in which they live. This study aims to describe the parenting pattern of career women in the neighborhood of rw.05 Cijerah Bandung and to find out the efforts made by parents of career women in improving the religious life of their children. This study uses a descriptive qualitative approach. Researchers collect data by means of questionnaires, interviews, observation and documentation. Determination of informants in this study using the technique of